Evaluation of ber cultivars against bark eating caterpillar (Indarbela sp.) under field condition (Indian Journal of Arid Horticulture, 2021)
Ber (Zizyphus mauritiana L.) is an important fruit crop cultivated under arid and semi-arid climatic conditions. The importance of bark eating caterpillar, Indarbela sp infesting to this crop has been recognized since many years. It is most devastating pest in ber growing areas. Plants frequently display genetic variation within and between population for traits that influence the preference and non- preference of insects on their hosts that are resistance traits (Johnson and Agrawal, 2005; Haldhar et al., 2017; Samadia and Haldhar, 2017; Muthusamy et al., 2017). Least susceptible cultivar is an economical and environment- friendly, farmer friendly and do not need much financial investment for insect management. Host plants play an important role in determining insect populations in respect to concentrations and proportions of nutrients, which differ among species (Schoonhoven et al., 2005). Direct defenses are mediated by plant characteristics that affect the herbivore's biology such as mechanical protection on the surface of the plants (e.g., hairs, trichomes, thorns, spines, and thicker leaves) that retard the development of herbivores (Hanley et al., 2007). Zizyphus nummularia provides a nutritious leaf fodder for the animals. The leaves contain 5.56 per cent DCP and 49.7 per cent TDN and are rich in protein and mineral matter. The fruits are believed to purify blood and to help in digestion. The bark is said to be a remedy in diarrhea. The root is used as decoction in fever and as powder applied to ulcer and wounds. The leaves form a plaster in strangury and are used in conjunctivitis. Besides providing the nutritious fruits, various parts of the ber tree are also known to have medicinal value (Bhandari, 1969; Kirtikar and Basu, 1975).
Keywords: loquat; Schoonhoven; cultivated